2022
DOI: 10.3389/fonc.2022.906824
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Levels of CRP and IL-6 and Decreased Frequencies of T and B Lymphocyte Subsets Are Associated With Immune-Related Adverse Events During Combination Therapy With PD-1 Inhibitors for Liver Cancer

Abstract: BackgroundProgrammed cell death protein 1/programmed death-ligand 1 (PD-1/PD-L1) immune-related adverse events (irAEs) are inevitable in patients with liver cancer. Although the incidence of severe irAEs is low, but can result in fatal consequences. To date, only a few commonly used clinical biomarkers have been reported.AimTo assess commonly used clinical biomarkers associated with the occurrence of irAEs to enable better management of irAEs by clinicians.MethodsWe retrospectively reviewed patients with liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…A similar increase in CD21 lo B cells after the first cycle of combination therapy, was reported in 23 renal cell carcinoma patients who experienced irAEs ( 117 ). Liver cancer patients treated with anti-PD-1 and tyrosine kinase inhibitors also showed decrease B cells in severe irAE patients ( 118 ).…”
Section: Autoantibodies and B Cells As Biomarkers Of Immune Related A...mentioning
confidence: 99%
“…A similar increase in CD21 lo B cells after the first cycle of combination therapy, was reported in 23 renal cell carcinoma patients who experienced irAEs ( 117 ). Liver cancer patients treated with anti-PD-1 and tyrosine kinase inhibitors also showed decrease B cells in severe irAE patients ( 118 ).…”
Section: Autoantibodies and B Cells As Biomarkers Of Immune Related A...mentioning
confidence: 99%
“…[22] [23] Regarding HCC treatment with anti-PD-1 Ab, the severity of irAEs is positively correlated with CRP and IL-6 and negatively correlated with the frequency of T and B lymphocyte subsets. [24] Our study found that CRP and NLR levels at the onset of liver-irAEs were higher in the irSC group. IL-6, which triggers the synthesis of is an in ammatory cytokine that plays an important role in immune processes and is involved in a variety of diseases including cancer.…”
Section: Discussionmentioning
confidence: 46%
“…Importantly, the changes in B cells preceded the development of clinical complications suggesting that they may be useful biomarkers for the initiation of preventive intervention or closer monitoring. Other studies in patients with liver cancer, renal cell cancer, or lung cancer patients have also described correlations between irAEs and similar changes in B cells including increase in CD21 lo B cells and plasmablasts in patients undergoing PD1 blockade or combination CTLA4 and PD1 checkpoint blockade 55–58 . Together, these studies support a possible role for B cells and particularly the CD21 lo Tbet + subset of human B cells in the pathogenesis of irAEs.…”
Section: B Cell Changes Following Checkpoint Blockade and The Risk Of...mentioning
confidence: 62%
“…Several studies have now reported a correlation between therapy‐induced changes in B cells or plasmablasts and increased risk for the development of irAEs 54–58 . One of the earliest studies in this regard was by Das et al, who studied patients with melanoma undergoing combination checkpoint blockade 54 .…”
Section: B Cell Changes Following Checkpoint Blockade and The Risk Of...mentioning
confidence: 99%